Capturing meanings of place, time and social interaction when analyzing human (Im)mobilities: Strengths and challenges of the application of (im)mobility biography - Kieslinger, Julia; Kordel, Stefan; Weidinger, Tobias (Forum qualitative Sozialforschung, 2020)
In this article, we suggest (im)mobility biography as a method for reconstructing human (im)mobilities and related negotiations of meanings of place, time and social interaction. Based on biographical-narrative approaches and participatory ideals the combination of life history interviewing with a participatory timeline tool is the best fit for capturing individuals' life-worlds over time. After presenting theoretical presuppositions on relational meanings of place, time and social interaction, we provide an overview of biographical and participatory research in the context of human (im)mobilities and sketch methodological origins of the life history interview and the timeline tool. Furthermore, we address issues essential for planning and preparing (im)mobility biography, and demonstrate two different applications of the method in migration contexts in Germany and Ecuador. Subsequently, we present options for analysis and interpretation of textual and graphical data outputs. Keeping in mind strengths and challenges, we consider (im)mobility biography a valuable method for capturing (im)mobile life-worlds as well as contextual embeddedness of individual decision-making on moving or staying. Especially in terms of its participatory orientation, the visualization of migration trajectories facilitates structuration and memorization of life histories, allows for shared analysis even at the interview stage, and encourages participants to reflect on their biographies.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Biographical research; Life history interview; Life-worlds; Migration studies; New mobilities paradigm; Participatory research; Qualitative research; Timeline tool

Encounters Between Experiences and Measurements: The Role of Local Knowledge in Climate Change Research - Kieslinger, Julia; Pohle, Perdita; Buitron, Viviana; Peters, Thorsten (Mountain Research and Development, 2019)
Innovative approaches could enhance scientific insights into how climate change affects mountain ecosystems and livelihoods and enrich climate action. Using an inter- and transdisciplinary approach in a remote tropical dry forest region of the Andes in southern Ecuador, this article combines local knowledge about climate change and adaptation, based on perceptions and experiences, with quantitative climate measurements. Our theoretical framework is based on the concept of vulnerability and sustainable livelihoods perspectives. Methodologically, we draw on the Participatory Rural Appraisal approach. Participatory workshops and qualitative interviews were carried out in the canton of Macara between 2015 and 2017. Local and regional climate data series were analyzed for climate trends and extreme events. Our study improves understanding of the social and physical dimension of climate change. Especially in mountain areas, differing scales of climate data must be considered to capture local climate conditions and changes. Thus, local knowledge could make a major contribution to selecting representative climate datasets, estimating local impacts of climate change, and developing adaptation policies.
CRIS-Team WoS Importer:2020-01-07

Impacts of COVID-19 on Venezuelan migrants in the Andean corridor - Kieslinger, Julia (International Migration, 2025)
Since 2015, about 7.9 million Venezuelans left their country due to political turmoil, socio-economic instability, and the ongoing humanitarian crisis. The Andean Corridor is the most frequented land route in South America. This article explores Venezuelan migrants' experiences with the COVID-19 pandemic on their journeys. Migrants undertake spatial movements and phases of staying, here conceived of as (im)mobilities. The study draws on crises and lifeworld perspectives, and uses participatory qualitative interviews to address individuals' decision-making under changing life conditions. The findings show that the governments' measures during the pandemic had severe impacts on the migrants, leading to forced (im)mobilization, changing mobility patterns, and means of transport. The informalization of (im)mobilities increased the risk of infection, endangered livelihoods, and resulted in greater exposure to insecurity and violence. The study highlights the need for inclusive, nuanced approaches to crises that acknowledge the voices and experiences of marginalized populations like Venezuelan migrants.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Venezuela; migration; crisis; (im)mobilities; South America; COVID-19 pandemic

Kulturgeographisches Geländepraktikum – Handbuch und Leitfaden. - Pohle, Perdita; Kieslinger, Julia; Kordel, Stefan; Geiselhart, Klaus (2015)

Kulturgeographisches Geländepraktikum – Leitfaden. Erlanger Skripte zum Geographiestudium - Gebauer, Matthias; Geiselhart, Klaus; Fürmaier, Peter; Haferburg, Christoph; Kaplan, Lena; Kieslinger, Julia; Kordel, Stefan; Kress, Martina; Lendl, Jonas; Orlowski, Benedikt Marko; Pohle, Perdita; Schnorr, Kristina; et al. (2015)

Perspectivas de la población local sobre condiciones y transformaciones socio-ambientales en el Cantón Macará (Provincia de Loja, Ecuador). Caso de estudio Sabiango - Kieslinger, Julia; Hualpa Erazo, Angel; Rengel Vega, Paola (2021)
As part of the doctoral thesis "The Importance of Spatial (Im)mobilities in the Context of Changing Life Conditions and Lifeworlds: The Example of Socio-Ecological Transformation in Rural Ecuador" (forthcoming), this report addresses the grassroots views of the participants in this research and gives them an arena to express their concerns about local living conditions and challenges. In a few sections, additional information from secondary data was included when it was considered of added value to the reader to embed the local participants’ views in a broader context. In order to implement the principles of the participatory research design, this report is dedicated to the local government administrations of the Parroquia Sabiango and the Cantón Macará (Ecuador) who can communicate and disseminate these findings among different actors in the field.<br

PROYECTO “ASISTENCIA INTEGRAL Y DE INCLUSIÓN SOCIAL A MIGRANTES Y COMUNIDADES DE ACOGIDA”. CASO DE ESTUDIO PROGRAMA CUERDA FIRME 2019 LIMA-PERÚ - Kieslinger, Julia; Buitrón Cañadas, Viviana; Hualpa Erazo, Angel; Rengel Vega, Paola (2020)
Como parte del proyecto “Asistencia integral y de inclusión social a migrante sy comunidades de acogida” se desarrolló el programa “Cuerda Firme 2019”, implementado por La Tarumba, en coordinación con la Cruz Roja Peruana, y con el apoyo de la Federación Internacional de Sociedades de la Cruz Roja y de la Media Luna Roja (IFRC), y el Alto Comisionado de las Naciones Unidas para los Refugiados (ACNUR). El objetivo general del estudio fue recopilar evidencia del programa Cuerda Firme 2019, desde la perspectiva de los participantes del programa, así como desde las organizaciones involucradas, con el fin de fomentar réplicas futuras, a nivel regional. Al mismo tiempo, los resultados podrían impulsar nuevas ideas o sugerencias de mejoras, para futuros proyectos, en cuanto a los objetivos y la visibilidad institucional de la Cruz Roja, en su función de fomentar espacios seguros a través de la creación de alianzas con organizaciones técnicas expertas.<br

Rechtliche und politische Rahmenbedingungen als Grundlage für sozial-ökologische Transformationen. Die Themenfelder Nachhaltigkeit, ländliche Räume, Klima- und Gewässerschutz, Biodiversität, Wald, Landwirtschaft und Energie - Pohle, Perdita; Brönner, Maximilian; Gerique-Zipfel, Andres; Kieslinger, Julia; Lederer, Lauritz (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2021)

The Importance of Spatial (Im)mobilities in the Context of Changing Life Conditions and Lifeworlds: The Example of Socio-Ecological Transformation in Rural Ecuador. - Kieslinger, Julia (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
Migration is an issue that is discussed intensively both on a global scale and in the Latin American context. It is commonly associated with wider socio-ecological transformation processes such as global change, urbanization and land use transitions. Rural areas are often considered as regions of out-migration, with out-migration is usually understood to be related to profound structural transformations. The present investigation is informed by insights from the dynamic and interdisciplinary fields of environment-migration nexus and migration-(rural) development nexus in the Global South, two fields that bring together scholars from environmental and climate science but also from social sciences and the humanities. Yet, since the inception of these fields of research, geographers have been participating in them, as they seem predestined to make a contribution that would bridge the gap between human and physical sciences (Felgentreff and Pott 2016). While scientific debates on environment-migration interlinkages predominantly revolved around external migration (Foresight 2011), discussions on migration-rural development interrelations emphasized internal rural-urban movements (Bilsborrow 2002). Within the vast fields, one common focus of interest was initially the environmental causation of migration (Hunter, Luna, and Norton 2015; Felgentreff and Pott 2016), whereas feedback effects of migration processes on rural sending areas tended to be underrepresented (Greiner and Sakdapolrak 2013). Scholars further pointed to the need for a greater consideration of the political, economic and social contextual factors that could influence both causes and effects of migration processes (Black et al. 2011). However, there is no consensus on how to conceptualize these contextual factors and how to integrate human-environment relations in migration theory (Hunter, Luna, and Norton 2015). With growing evidence from case studies in different geographical settings, academics increasingly addressed migration as a form of adaptation to environmental change and a household strategy of risk minimization (e.g. McLeman 2014). This point of view challenges the widespread notion of ‘passive’ or ‘forced’ migrants, which neglects migrants’ agency in decision-making and their potential role in the development of coping strategies. However, despite there also always having been people who remained in the investigated areas of out-migration, the phenomenon of staying put has been and still is starkly underrepresented in research (except some examples, for instance Mata-Codesal 2015; Mata Codesal 2016 for Latin America) – and especially with regard to environment and rural development interlinkages. Apart from content-related issues, there is an epistemological and methodological issue that represents a major shortcoming: both fields have been and still are dominated by external scientific views and do not sufficiently take into account the experiences of the people concerned. The present doctoral thesis in the field of human geography aims to push these debates forward and to contribute to the aforementioned shortcomings. For this reason, this investigation addresses the diversity of people’s movements without predefined spatial and temporal categories and takes into account the phenomenon of staying, which in the following is termed and conceived of as human (im)mobilities (New Mobilities Paradigm, e.g. Sheller and Urry 2006). Further, the causes and feedback effects of these (im)mobilities are equally considered in order to capture interrelated socio-ecological transformations. Owing to a social constructivist research perspective, the focus is set on the everyday knowledge of actors from the field and how they construct social meanings. This investigation thus aims to grasp the participants’ views on interrelations between human (im)mobilities and changing living contexts (e.g. environmental changes, household dynamics). The overarching research question is set as follows: From the perspective of the local population, what role do (im)mobilities of people play as a cause of and driver for changing living contexts and what is the significance of human (im)mobilities for rural livelihoods and everyday practices? A place based study is the best way to address the complexity of human (im)mobilities and their interrelations with socio-ecological transformations. The Cantón of Macará in southern Ecuador was selected as a study area because various authors had observed historically high out-migration in general (Temme 1972; Bilsborrow et al. 1987; Gray 2009a) and for climatic reasons, specifically during the droughts of the 1960s (Temme 1972; OAS 1994). Nowadays, the municipality of Macará has highlighted in its local development agenda 2015-2019 the out-migration of population as an urgent field of action and points to climatic changes, recurring extreme events as well as the degradation of arable lands and tropical dry forests as major challenges for the rural livelihoods in the canton (GAD Macará 2015). Further, the study area is located in the western escarpment of the Andes, an area expected to be highly affected by the impacts of climate change in the future (IPCC 2014a; Kaenzig and Piguet 2014; Schoolmeester et al. 2016). In order to carry through a people-centered research, I developed a research design that draws methodologically on the participatory research paradigm (e.g. Bergold and Thomas 2012) and on grounded theory procedures (Glaser and Strauss 1967; Charmaz 2006). The aim was to enable knowledge co-production in a collaborative research process representing the variety of actors relevant in the field. For this, strategies and new tools were elaborated with special emphasis on actors’ involvement, the reduction of power inequalities and immersion into the field (Kieslinger, Kordel, and Weidinger 2020, annex #2FQS). Consequently, this investigation required high flexibility, openness and the steady adaptation of proceedings and, finally, time and financial resources. The peculiarity of this investigation is its processual character, a direct result of its intentions. Firstly, initial aims and research questions were adapted according to new insights based on scientific perspectives and participants’ priorities. Secondly, methods for data generation were jointly elaborated with co-investigators and adjusted according to the participants’ interests, capabilities and needs. Thirdly, the participants’ grassroots views were contrasted with scientific findings about interlinkages between migration, environment and rural development in the Global South. Fourthly, the issues under study were approached as openly as possible and without predefined theoretical concepts in order to make a contribution to theory formation by means of own empirical findings. Findings of this doctoral thesis provide empirical evidence of the importance of human (im)mobilities and interrelated socio-ecological transformations in rural Ecuador. Three levels of analysis were considered: study area, household and individuals in social structures. Findings from these distinct analytical levels were combined to get a more profound understanding of the emerging concepts and categories used by the participants. In line with the participants’ perspectives, two core categories were identified: “(im)mobilities in everyday life” and “(im)mobilities related to changing places of living”. Mobilities of people in everyday life are closely intertwined with practices to secure livelihoods and satisfy basic needs. This relates to routines in the closer surroundings of the place of living (e.g. for water management, agricultural production, forest use and conservation, social organization, purchase and sale of products, education, work, medical treatments, recreation and religion) and occasional mobilities to cities like Loja, Cuenca, Guayaquil and Quito (e.g. for medical treatments, administrative procedures at public institutions, family visits). Distinct (im)mobilities and practices in everyday life depend on individuals’ roles and memberships, gender and age, but also to the distance of places and public infrastructures. The overall participants’ observation of population decline and changes in population structure has been associated with a continuous trend of people’s mobilities related to changing places of living. The results of the historical analysis (1960-2017) show that there has been a continuous trend of out-migration with changing patterns according to common destinations. These patterns could be grouped under the categories of domestic rural-rural and rural-urban as well as external movements. Findings provide evidence that grasping the historical context of the respective period and the events and trends occurring during a certain period of time is of vital importance to understand human (im)mobilities. Events and trends unfold in different spatial and temporal dimensions, as well as in political, economic, ecological and social contexts while different events and trends may overlap or interact with each other. Over time, mobility processes of people from the study area have become more diverse and complex due to translocal and/or -national networks. Based on young peoples’ statements, it can be assumed that the trend of out-migration will continue in the future. It also appeared that domestic rural-urban movements are nowadays the dominant pattern. The motivations expressed by participants encompass education, personal development and self-realization as well as work were quite homogeneous and are closely interrelated. However, participants also highlighted that there have always been people who remained in the study area, even in crisis situations. Further, movement patterns changed despite events of the same kind repeatedly occurring (e.g. droughts), with individuals opting for different destinations than the common ones. Findings of this thesis show that there are no linear cause-effect relations, but common issues of concern which the participants relate to human (im)mobilities. The comparison of findings from different analytical units (study area, household, individual) demonstrates the complexity of multiple drivers and multidimensional interactions that shape human (im)mobilities. In order to fully understand people’s mobilities and immobilities, I undertook an in-depth examination of decision-making processes on leaving and staying as well as the selection of places for living. At the individuals’ level, I was able to demonstrate that mobility processes are neither unique endeavors nor simply unidirectional, resulting in complex spatial patterns, while immobilities occurred at distinct places during different phases of staying. Further, the results show that decision making is a negotiation process, wherein certain issues of interest such as social relations, financial income and investments, agricultural production, risk and security, experiences and knowledge are taken into account. Additionally, these negotiations are constantly adapted to individuals’ perspectives on past, present and future, living here and there as well as self-realization and social interaction. After combining these findings with a literature review (Kieslinger, Kordel, and Weidinger 2020, annex #2FQS), decision-making on leaving and staying has been conceived as a process of negotiations based on relational meanings of place(s), (life) time(s) and social interaction(s). By putting mobile and immobile persons as agents of their own lives center stage and focusing on the meaningful living contexts in which they are situated when negotiating and enacting (im)mobilities, I could develop a new conceptual framework to address both agency and contextual factors in migration environment and rural development interrelations. For this, I draw on spatial human (im)mobilities as conceived of by the New Mobilities Paradigm (e.g. Sheller and Urry 2006) and use the life conditions and lifeworlds concepts of Björn Kraus (2015) to conceptualize the living context. In doing so, I conclude that life conditions determine the opportunities and constraints of human (im)mobilities, whereas lifeworlds as the subjective constructions of reality under these conditions are the basis for decision-making on leaving and staying; life conditions, but also mobilities and immobilities are constantly re-evaluated. Consequently, lifeworlds are highly dynamic and influenced by experiences concerning (im)mobilities. In this framing social meanings of (im)mobilities can be accessed by approaching lifeworlds and vice versa.<br
Keywords: grounded theory; human spatial (im)mobilities; life conditions and lifeworlds; migration - (rural) development nexus; migration - environment nexus; new mobilities paradigm; participatory research; rural Ecuador; socio-ecological transformations

The road to integrate climate change projections with regional land-use–biodiversity models - Cabral, Juliano Sarmento; Mendoza-Ponce, Alma; da Silva, André Pinto; Oberpriller, Johannes; Mimet, Anne; Kieslinger, Julia; Berger, Thomas; Blechschmidt, Jana; Brönner, Maximilian; Classen, Alice; Fallert, Stefan; Hartig, Florian; et al. (People and Nature, 2023)
Current approaches to project spatial biodiversity responses to climate change mainly focus on the direct effects of climate on species while regarding land use and land cover as constant or prescribed by global land-use scenarios. However, local land-use decisions are often affected by climate change and biodiversity on top of socioeconomic and policy drivers. To realistically understand and predict climate impacts on biodiversity, it is, therefore, necessary to integrate both direct and indirect effects (via climate-driven land-use change) of climate change on biodiversity. In this perspective paper, we outline how biodiversity models could be better integrated with regional, climate-driven land-use models. We initially provide a short, non-exhaustive review of empirical and modelling approaches to land-use and land-cover change (LU) and biodiversity (BD) change at regional scales, which forms the base for our perspective about improved integration of LU and BD models. We consider a diversity of approaches, with a special emphasis on mechanistic models. We also look at current levels of integration and at model properties, such as scales, inputs and outputs, to further identify integration challenges and opportunities. We find that LU integration in BD models is more frequent than the other way around and has been achieved at different levels: from overlapping predictions to simultaneously coupled simulations (i.e. bidirectional effects). Of the integrated LU-BD socio-ecological models, some studies included climate change effects on LU, but the relative contribution of direct vs. indirect effects of climate change on BD remains a key research challenge. Important research avenues include concerted efforts in harmonizing spatial and temporal resolution, disentangling direct and indirect effects of climate change on biodiversity, explicitly accounting for bidirectional feedbacks, and ultimately feeding socio-ecological systems back into climate predictions. These avenues can be navigated by matching models, plugins for format and resolution conversion, and increasing the land-use forecast horizon with adequate uncertainty. Recent developments of coupled models show that such integration is achievable and can lead to novel insights into climate–land use–biodiversity relations. Read the free Plain Language Summary for this article on the Journal blog.
CRIS-Team Scopus Importer:2023-06-02
Keywords: agent-based models; biodiversity response; environmental change; indirect effects; integrative approaches; mechanistic models; socio-ecological systems; species richness

Unravelling the meaning of place and spatial mobility: analysing the everyday life-worlds of refugees in host societies by means of mobility mapping - Weidinger, Tobias; Kordel, Stefan; Kieslinger, Julia (Journal of Refugee Studies, 2019)
This article develops mobility mapping as a valuable space-related instrument to tackle the lack of attention to the meanings of places and everyday spatial mobility in the process of refugee settlement. Referring to two consecutive case studies carried out with asylum seekers and recognized refugees in rural Germany, we discuss the surplus of this tool considering both peculiarities in implementation and the opportunities of analysis of respondent-generated maps. Experiences from this trial research point out ways of implementing a tool that focuses on the graphic and visual dimension of knowledge creation. Relying on principles of participatory research, this tool can help to diminish power asymmetries between the researcher and the participant and acknowledge individuals’ competencies in terms of language. Depending on the aim of the study, the empirical data generated can be analysed both as a product and as a process. Results indicate added value by revealing the importance of spatial dimensions in asylum seekers’ and refugees’ life-worlds, encompassing the construction of individually important places as well as spatial mobility and accessibility. For practitioners, the implementation of the tool provides an opportunity to enhance participant-oriented planning and capacity building, such as in terms of networks and infrastructures, that addresses both individuals’ needs and spatial structures.<br
Keywords: Mobility; access; exclusion; everyday life; rural areas; participatory research

Veränderungen der landwirtschaftlichen Nutzung in Bayern seit 1999. Spielt der Klimawandel eine Rolle? - Kieslinger, Julia; Brönner, Maximilian; Austermühl, Carina; Pohle, Perdita (Herausforderungen des Klimawandels in Bayern., 2021)
Vor dem Hintergrund des Klimawandels als potenzieller Einflussfaktor diskutiert der vorliegende Artikel Veränderungen in der landwirtschaftlichen Nutzung in Bayern seit 1999. Mit Hilfe einer raum-zeitlichen Sekundärdatenanalyse wird ein Überblick über Flächenentwicklungen und Erntedynamiken gegeben. Neben der Abnahme der landwirtschaftlichen Nutzfläche insgesamt, wurde bei den Dauergrünlandflächen ein bayernweiter Rückgang und bei den Ackerflächen eine Abnahme in den nördlichen/östlichen sowie eine Zunahme in den südlichen/westlichen Landkreisen deutlich. Eine Flächenzunahme ist bei Weizen, Silomais und Körnermais zu verbuchen. Die Ernteerträge lagen im Jahr 2019 bei allen Kulturpflanzen, abgesehen von Kartoffeln und Silomais, höher als im Jahr 1999. Ertragseinbußen wurden besonders in den Jahren 2003, 2013, 2015 und 2018 deutlich, die von Niederschlagsmangel, Trockenheit, überdurchschnittlich hohen Temperaturen und vielen Hitzetagen in den Sommermonaten geprägt waren. Ein Zusammenhang zwischen dem Klimawandel und der landwirtschaftlichen Nutzung in Bayern ergibt sich vor allem indirekt über klimapolitische Maßnahmen (Erneuerbare-Energien-Gesetz) und deren Folgen in den Flächenentwicklungen (Zunahme Maisanbau). Außerdem korrelieren die Ertragseinbrüche im Ackerbau mit den in den vergangenen zehn Jahren gehäuft aufgetretenen Witterungsextremen. In der landwirtschaftlichen Produktion werden Anpassungsmaßnahmen im Umgang mit Klimafolgen und Extremwetterereignissen zunehmend wichtiger.<br
Keywords: Bayern; Klimawandel; Witterungsextreme; landwirtschaftliche Nutzung; Flächenentwicklungen; Erntedynamiken

What is a Batey? Origins and Trajectories of an Antillean Concept - Kieslinger, Julia; Dohardt, Raphael; Jansen, Silke; Kordel, Stefan (Journal of Latin American Geography, 2024)
This article explores the meaning of the term “batey,” which can be broadly defined as a distinct type of settlement in the Dominican Republic, closely linked to sugar cane cultivation and transnational migration dynamics with Haiti. Drawing on historical documentation, we examine semantic changes in the term, from its pre-Columbian origins through the colonial period to the present. We also present contemporary emic perspectives on what constitutes a batey—views obtained from interviews with inhabitants of 28 Dominican bateyes. Additional information was drawn from (participant) observation in 96 bateyes. From this, we deduced the recent trajectories of bateyes, which fosters our understanding of the interrelated dynamics of rural development, intersecting forms of migration, e.g. domestic and transnational, and the impact of globalization on local communities, as well as the persistent impact of colonialism on local societies and economies. Furthermore, we address power imbalances by taking intoaccount postcolonial perspectives and giving voice to batey inhabitants and migrants. Our findings may serve as a point of departure for further research from a postcolonial perspective on the marginalization and stigmatization of settlements with transnational dynamics.<br
Keywords: Dominican Republic; Haiti; transnational spaces; postcolonial perspectives; socio- cognitive linguistics

YOUNG PEOPLE'S VISIONS FOR LIFE IN THE COUNTRYSIDE IN LATIN AMERICA - De La Vega-Leinert, A. Cristina; Kieslinger, Julia; Jimenez-Moreno, Marcela; Steinhauser, Cornelia (Geographical Review, 2021)
Abtract Young people steer their life trajectories against the backdrop of profound transformations of rurality. They are considered protagonists in the present and future of rural areas; however, their experiences and perspectives on life in, and away from, the countryside have been scarcely acknowledged in academia. Considering conceptual thoughts on new mobilities, place-based belonging, and new ruralities, we argue that young people are a highly dynamic and continually reassessing group. In four case studies realized independently in Argentina, Bolivia, Ecuador, and Mexico, we closely involved young people with multiple participative methods to express their perceptions, concerns, and demands. We experiment on ways to integrate our insights for future comparative studies. Beyond the diversity in local contexts, we found convergences in young people's visions, which motivate them to stay or leave, with wider implications for the sustainability of rural places. "Living in between" thereby encapsulates multifaceted hybrid possible countrysides away from constraining dichotomic views.
CRIS-Team WoS Importer:2021-06-25